Visible-light-prompt photoelectrochemical sensor of copper(II) ions based on CdS nanorods modified with Au nanoparticles and graphene quantum dots - Ibrahim, Izwaharyanie; Lim, Hong Ngee (2018)
Excessive consumption of Cu2+ ions can cause damage to liver and kidney. Thus, significant efforts have been devoted to detecting Cu2+ ions in the environment and biological systems. An interconnected triplet structure of CdS/Au/GQDs was designed as the photo-to-electron conversion medium for real-time and selective visible-light-prompt photoelectrochemical (PEC) sensor of Cu2+ ions in real-water samples. The synergistic interaction of CdS/Au/GQDs enabled smooth transportation of charge carrier to the charge collector, providing a channel to inhibit the charge recombination reaction. Moreover, the presence of Cu2+ ion on the photoelectrode activated the quenching of the charge transfer efficiency, thus promoting sensitive PEC determination of Cu2+ ions level. The real-time monitoring of Cu2+ ions in mineral water, tap water and reverse osmosis water were performed with satisfactory results, confirming the capability of the as-fabricated photoelectrode as a practical detector for trace element of Cu2+ ions.